2006
DOI: 10.3102/00346543076002173
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Recruitment and Retention: A Review of the Recent Empirical Literature

Abstract: This article critically reviews the recent empirical literature on teacher recruitment and retention published in the United States. It examines the characteristics of individuals who enter and remain in the teaching profession, the characteristics of schools and districts that successfully recruit and retain teachers, and the types of policies that show evidence of efficacy in recruiting and retaining teachers. The goal of the article is to provide researchers and policymakers with a review that is comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
642
2
29

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 835 publications
(733 citation statements)
references
References 86 publications
15
642
2
29
Order By: Relevance
“…Moreover, high rates of attrition of teachers in their first five years of teaching (Darling-Hammond, 1997;Ingersoll, 2003;Kados & Johnson, 2007;Burghes et al, 2009;Shen and Palmer, 2009;OECD, 2005 and remain a persistent teacher retention problem. Although some studies show that on average, early career leavers tend to be less effective than stayers as measured by the test score gains of the students in their classrooms (Henry et al, 2011;Goldhaber et al, 2011;Boyd et al, in press), others suggest that teachers with stronger qualifications and more competitive university backgrounds are more likely to exit early (Lankford et al, 2002;Boyed et al, 2005;Guarino et al, 2006;Feng and Sass, 2011).…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high rates of attrition of teachers in their first five years of teaching (Darling-Hammond, 1997;Ingersoll, 2003;Kados & Johnson, 2007;Burghes et al, 2009;Shen and Palmer, 2009;OECD, 2005 and remain a persistent teacher retention problem. Although some studies show that on average, early career leavers tend to be less effective than stayers as measured by the test score gains of the students in their classrooms (Henry et al, 2011;Goldhaber et al, 2011;Boyd et al, in press), others suggest that teachers with stronger qualifications and more competitive university backgrounds are more likely to exit early (Lankford et al, 2002;Boyed et al, 2005;Guarino et al, 2006;Feng and Sass, 2011).…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
“…This has meant that, unfortunately, children in countries needing teachers the most, tend to be taught by the least qualified personnel (UNESCO, 2006). In contrast, in the developed world, such as the USA, the UK and many European countries, shortage of teacher supply tends to be a particularly pressing problem for core subject areas such as maths, modern foreign languages and science (European Commission, 2012) and for schools serving socioeconomically deprived communities (Ingersoll, 2001;Guarino et al, 2006;Boyd et al, 2008). Grissom's (2011) study found that higher teacher turnover rates in disadvantaged schools result in part from the ineffectiveness of the principal.…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
“…Pour finir, citons le cas des revues de littérature, telles que celles de Bloland and Selby (1980), Borman and Dowling (2008), Guarino et al (2006), Scheopner (2010), Macdonald (1999) et la présente, qui constituent des éléments importants de la recherche sur le décrochage dans la mesure où elles centralisent, organisent et mettent en lien différents résultats empiriques, ce qui permet d'améliorer la compréhension du phénomène de décrochage et d'esquisser des pistes de recherches futures.…”
Section: Le Décrochage Enseignant : Une Problématique Internationaleunclassified
“…Des conditions de travail insatisfaisantes : ce facteur renvoie aux conditions de travail d'ordre matériel, administratif ou financier (Buchanan 2010;Guarino et al 2006;Loeb et al 2005). La faiblesse du salaire (Billingsley 2004;Buchanan 2010;Certo and Fox 2002;Clotfelter et al 2008;Dolton and Van der Klaauw 1999;Gonzales 1995;Gonzalez et al 2008;Guarino et al 2006;Hahs-Vaughn and Scherff 2008;Ingersoll 2001;Macdonald 1999;McCreight 2000) est l'aspect le plus cité.…”
Section: Résultats : Identification Des Facteurs Possibles Du Décrochunclassified
“…However, there is a scarcity of literature examining the combined issues of teacher recruitment and retention with teacher quality (Guarino, Santibañez, & Daley, 2011). Two factors contributing to the paucity of information on teacher quality and attrition were (1) a lack of a common definition for teacher quality; and (2) the scarcity of data that would aid researchers in identifying effective teachers and the factors influencing the recruitment and retention of effective teachers (Guarino et al, 2011). The lack of literature on teacher quality related to teacher attrition was corroborated by Rivkin et al (2005) and Krieg (2006).…”
Section: Teacher Quality and Attritionmentioning
confidence: 99%